2015
DOI: 10.1155/2015/350750
|View full text |Cite
|
Sign up to set email alerts
|

Full Anatomical Recovery of the Dopaminergic System after a Complete Spinal Cord Injury in Lampreys

Abstract: Following a spinal injury, lampreys at first are paralyzed below the level of transection. However, they recover locomotion after several weeks, and this is accompanied by the regeneration of descending axons from the brain and the production of new neurons in the spinal cord. Here, we aimed to analyse the changes in the dopaminergic system of the sea lamprey after a complete spinal transection by studying the changes in dopaminergic cell numbers and dopaminergic innervation in the spinal cord. Changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…We show that, in lampreys, the drastic initial decrease in the number of glutamate-ir cells and processes in response to a complete spinal cord lesion is followed by an almost complete recovery of the system; with the exception of the CSFc cells that are never recovered, even at 24 wpl. This is in contrast with the dopaminergic system, which undergoes full anatomical recovery following a complete injury at the same spinal cord level in lampreys34. However, the serotonergic system of lampreys also shows an incomplete recovery after SCI26.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We show that, in lampreys, the drastic initial decrease in the number of glutamate-ir cells and processes in response to a complete spinal cord lesion is followed by an almost complete recovery of the system; with the exception of the CSFc cells that are never recovered, even at 24 wpl. This is in contrast with the dopaminergic system, which undergoes full anatomical recovery following a complete injury at the same spinal cord level in lampreys34. However, the serotonergic system of lampreys also shows an incomplete recovery after SCI26.…”
Section: Discussionmentioning
confidence: 89%
“…However, neuronal overproduction after SCI in zebrafish is much larger, up to 5-fold the number of neurons in control animals29. By contrast, the number of dopaminergic neurons after SCI in lampreys increases progressively until reaching levels similar to those found in un-lesioned animals, but without an initial phase of overproduction of dopaminergic neurons34. This highlights the importance of studying the behaviour of neurons with different neurotransmitter phenotypes to decipher how they respond to the injury and their contribution to functional restoration after a lesion.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Positive in situ signal in sea lamprey brain sections had a granular appearance probably due to low expression of these mRNAs in each single cell of the sea lamprey. Previous studies looking at the expression of different neurotransmitter receptors in lampreys have shown that the in situ hybridization signals appeared as a dotted labeling in sections of the CNS: serotonin receptor 1A (Cornide-Petronio et al, 2013, 2014), dopamine receptor D2 (Robertson et al, 2012; Fernández-López et al, 2015), and dopamine receptor D4 (Pérez-Fernández et al, 2016); suggesting that low expression levels are a common feature of different metabotropic neurotransmitter receptors.…”
Section: Discussionmentioning
confidence: 98%
“…Data sources: Amphioxus; GABAergic neuron, serotonergic neuron, dopaminergic neurons not found in spinal cord, no data on other types of neurons. Lamprey; glutamatergic, glutamate‐glycine, glutamate‐GABA neurons, dopamine‐GABA neurons, dopamine neurons, dopamine‐glutamate neurons, aspartate, aspartate‐GABA neurons, glycine, glycine‐GABA neurons, cholinergic neurons . Larval data instead of adult for serotoninergic and GABAergic neurons .…”
Section: Outgroups and Evolutionary Origins: Spinal Cords Cell Typesmentioning
confidence: 99%